2007
DOI: 10.1021/ar600001b
|View full text |Cite
|
Sign up to set email alerts
|

Bioinorganic Chemistry of Bismuth and Antimony:  Target Sites of Metallodrugs

Abstract: The biocoordination chemistry of antimony and bismuth has been extensively investigated due to the historical use of these metals in medicine. Structures of bismuth antiulcer agents and interactions of Bi3+ with proteins and enzymes, such as transferrin and lactoferrin, the histidine-rich protein Hpn, and urease, have been characterized. Sb5+ is a prodrug and is bioreduced or activated to its active form Sb3+ intracellularly. Antimony binds to biomolecules, such as glutathione, trypanothione, and nucleotides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
132
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 201 publications
(140 citation statements)
references
References 46 publications
0
132
0
2
Order By: Relevance
“…Previously, we characterized the structure of CBS, the recognition of Bi 3ϩ by the iron and zinc storage proteins, and recently the histidine-rich protein Hpn (20,34,(51)(52)(53). Using a metalloproteomic approach, we screened both Ni 2ϩ -and Bi 3ϩ -binding proteins in H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we characterized the structure of CBS, the recognition of Bi 3ϩ by the iron and zinc storage proteins, and recently the histidine-rich protein Hpn (20,34,(51)(52)(53). Using a metalloproteomic approach, we screened both Ni 2ϩ -and Bi 3ϩ -binding proteins in H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Although the antimicrobial activity of bismuth against H. pylori has been demonstrated (19), the mechanism of the action is not well understood. A number of proteins and enzymes have been demonstrated previously as intracellular targets of bismuth (20). Using a metalloproteomic approach, it was found that intracellular levels of four proteins (HspA, HspB, NapA, and TsaA) were significantly up-or down-regulated after bismuth treatment (21), and thus bismuth-binding proteins in H. pylori were identified.…”
mentioning
confidence: 96%
“…Under highly acidic conditions, the activities of urease in the wild-type strain increased three times compared with those in the mutant strains, thereby supporting the idea of Hisrich proteins (Hpn and Hpnl) as nickel reservoirs. [15] Hpnl protein, which consists of a histidine-rich domain and two glutamine-rich motifs (Figure 1), [16] was previously Abstract: The Hpn-like protein (Hpnl), a histidine-and glutamine-rich protein, is critical for Helicobacter pylori colonization in human gastric muscosa. In this study, the thermodynamic properties of Ni II , Cu II , Co II , and Zn II toward Hpnl were studied by isothermal titration calorimetry (ITC).…”
Section: Introductionmentioning
confidence: 99%
“…Various antimony compounds find continued use in the treatment of tropical diseases, most notably leishmaniasis caused by Leishmania species, which are human protozoan parasites of the trypanosomatidae family [50][51][52][53][54]. The two most prominent antimony compounds used in the treatment of cutaneous and visceral leishmaniasis are sodium stibogluconate (XIX, Pentostam) and meglumine antimonate (XX, Glucantime): their molecular compositions let alone precise molecular structures remain uncertain [55].…”
Section: Antimony Compoundsmentioning
confidence: 99%